ETANOLISIS MINYAK SAWIT DENGAN KATALISATOR KALIUM HIDROKSID DAN PENAMBAHAN UREA DALAM SEBUAH REAKTOR ALIR TANGKI BERPENGADUK DITINJAU DARI SEGI KINETIKA = Kinetics of Ethanolysis of Palm Oil Using Potassium Hydroxide ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Several research works have been done to increase the conversion of ethanolysis of fatty oil by displacing the equilibrium to the right. However, some more improvements might be required. In this study, urea was added to the reaction mixture to bind the glycerol formed, so that the reversible reaction could be shifted to the right. Ethanolysis of palm oil was initiated with heating the palm oil in the reactor. At the same time, ethanol containing a certain amount of potassium hydroxide was heated in another vessel. As soon as the desired reaction temperature was reached, the two reactants and urea were mixed quickly in the reactor. Afterwards, the palm oil, urea, and the ethanol containing potassium hydroxide were introduced into the reactor continuously and the product flowed out of the reactor through an overflow system. The glycerol contents of the products were determined with a refractometer, and then with Gas Chromathograpy. The experimental data showed that the rate of ethanolysis of palm oil was controlled by chemical reaction. The heterogeneous reaction model was more suitable to describe the kinetic of the reaction. The addition of urea to the reaction mixture increased the conversion 17 % compared to that without urea. The highest conversion (82,05%) was reached at temperature of 348 K, stirring speed of 800 rpm, the addition of 1 % potassium hydroxide, and 5 % urea. The property of ester produced approached the specification of diesel oil except for its viscosity.